Airpower for strategic effect - Gray, Colin S.; Air University (U.S.). Press; Air University (U.S.). Air Force Research Institute (Maxwell Air Force Base, Alabama : Air University Press, Air Force Research Institute, 2012)
"Airpower for strategic effect is intended to contribute to the understanding of airpower -- what it is, what it does, why it does it, and what the consequences are. This is the plot: airpower generates strategic effect. Airpower's product is strategic effect on the course of strategic history. Everything about military airpower is instrumental to the purpose of securing strategic effect."--P. xv.
"February 2012."
Format not distributed to depository libraries.
Second printing has: "First printing February 2012; Second printing July 2014"--title page verso.
Includes bibliographical references (pages [317]-346) and index.
Also available via the Internet.
Keywords: Air power -- United States -- History; History